Chemical analysis of airborne particulates for air pollutants in chiang mai and lamphun provinces, thailand - Somporn Chantara (2018)
Concentrations of airborne particulate matters with diameter less than 10 μm (PM10) were measured for 24 hours every 3 days at four sampling stations located in Chiang Mai and Lamphun Provinces, Thailand. The sampling scheme was conducted during June 2005 to June 2006. The result revealed the same pattern for all stations, in which the PM10 concentration increased at the beginning of dry season (December) and reached its peak in March before decreasing by the end of April. The mean PM10 concentrations were in the range from 33.17 ±21.39 μg/m3 in rainy season to 73.64 25.34 μg/m3 in dry season. The analysis for air pollutants in particulate matters was carried out in order to determine polycyclic aromatic hydrocarbons (PAHs) by GC-MS, major dissolved ions by IC, some metals and elements by ICP-OES and total carbon by CHN/S/O analyzer. Mean concentration of total PAHs was in a range from 1.7- 12.2 ng/m3. Ratio of non-carcinogenic and carcinogenic PAHs found was about 1:3 and 1:4 depending on sites. Maj r dissolved ions bound with PM10 were ammonium and sulfate ions. More than half of the water dissolved samples had the pH value less than 5.6. High concentrations of potassium, iron, calcium, silicon and aluminum were found in dry season, while low concentration of toxic metals such as arsenic, cadmium, mercury and lead was found only in some samples. Concentrations of most of carcinogenic PAHs, some metals, ions and total carbon were found to be positively correlated to PM10 concentrations. Seasonal variation of air pollutants based on PM10 composition was obviously observed. It was changed from higher amounts to lower amounts in the following order: dry season (December-March), transition periods (April-May and October-November) and wet season (June-September), which corresponded to the amounts of PM10 contaminated in the atmosphere. Spatial variation was not much observed except for one sampling site, where PAHs content was significantly higher than another sites. Apart from traffic congestion, this was p obably due to specific local activities i.e. biomass burning.